Aksi Kamisan; Tolak RUU TNI sebagai Representasi Pemuda dan Gerakan Sosial menurut Perspektif Charless Tilly - Hilda Lolita Putri; Irfan Khairan Ali; Wanda Aziza; Yoga Parulian Panggabean (Institut Nalanda, 2025)
This study discusses Aksi Kamisan as a contemporary social movement initiated by youth, particularly in the Jember region, aimed at rejecting the Military Bill (RUU TNI) and advocating for the enforcement of human rights (HAM). Using a qualitative approach with a phenomenological method, this research analyzes Aksi Kamisan through Charles Tilly’s theory of social movements, which includes the elements of campaigns, repertoires of contention, and WUNC display (worthiness, unity, numbers, commitment). The findings indicate that Aksi Kamisan in Jember represents a collective, symbolic, and peaceful struggle, with active participation from university students across campuses as the primary actors. This action not only voices opposition to repressive state policies but also fosters solidarity among citizens in defending democracy and human rights. The movement’s sustainability, participants’ moral strength, and strategic communication and consolidation are key to reinforcing its resilience and influence on both the public and government.